2017
DOI: 10.1123/jmld.2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Product- and Process-Oriented Measures of Motor Competence and Perceived Competence

Abstract: Motor competence is associated with psychological and physical health outcomes. A reciprocal relationship between motor competence and perceptions of physical competence exists, but the developmental trajectory of the motor competence/perceived competence relationship is not well understood. Standardized assessments take a product- or process-oriented approach, but research concerning the motor competence/perceived competence relationship is limited to using process-oriented assessments. It is unknown whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 0 publications
3
36
0
6
Order By: Relevance
“…Perceived physical competence is suggested to be comprised of interactions within different PA environments . The development of perceived physical competence specifically aligns with the development of competence in MC as children's cognitive capacity to understand their own competence improves across time . However, a recent article of Estevan et al suggested there is a controversy in the literature based on what concept researchers are attempting to address when referring perceived physical competence (eg, perceived physical competence, perceived motor competence, perceived motor proficiency, perceived physical ability, perceived physical self‐concept, perceived sports/athletic competence).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived physical competence is suggested to be comprised of interactions within different PA environments . The development of perceived physical competence specifically aligns with the development of competence in MC as children's cognitive capacity to understand their own competence improves across time . However, a recent article of Estevan et al suggested there is a controversy in the literature based on what concept researchers are attempting to address when referring perceived physical competence (eg, perceived physical competence, perceived motor competence, perceived motor proficiency, perceived physical ability, perceived physical self‐concept, perceived sports/athletic competence).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal data also demonstrates the long‐term impact of perceived physical competence (ie, sports competence and physical competence) on physical activity from childhood into adolescence . Importantly, it is hypothesized that the strength of association between perceived physical competence and physical activity may increase as children age, perhaps as a consequence of the concomitant increase in strength of associations between actual MC and perceived physical competence …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal research has identified perceived MC as a mechanism through which motor skill proficiency in childhood contributes to a physically active and healthy lifestyle in adolescence [25][26][27][28]. Given the influence that both actual and perceived MC in childhood can have as health determinants, empirical research has focused on furthering our understanding of their dynamic and changing relationship throughout childhood and adolescence [6,29].…”
Section: Introductionmentioning
confidence: 99%
“…Contentiously, many studies show that girls outperform boys in locomotor skills [26,38,39], whilst a comparable number of studies assert that boys have equal [40,41] or higher locomotor skill competence [42]. Concerning the perception of MC, sex differences seem to proliferate during child development [29,43,44]. Whilst some studies report that boys and girls around the pre-school years display equal perceptions of competence, from primary school years onward, higher self-perceptions in boys are consistently found [29,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%